ANALISA KEPUASAN PELANGGAN DALAM KUALITAS PELAYANAN DAN HARGA TERHADAP LOYALITAS PADA PENGGEMAR GRUP MUSIK - Dohan Faqih Ibrahim; Siti Mariam; Ahmad Hidayat Sutawijaya; Abdul Haeba Ramli (JURNAL LENTERA BISNIS, 2025)
The purpose of this research is to determine how the analysis of customer satisfaction in service quality and price affects loyalty among music group fans. This research method uses a descriptive method with a quantitative approach. The sampling technique used was purposive sampling technique, and the data collection method in this research used observation and questionnaires. Data obtained from the questionnaire with a total of 120 respondents. The testing of the questionnaire data used SPSS version 26 for the calculations, with a significance level of a = 5% for this test. The results of this study indicate that customer satisfaction, service quality, and price significantly affect fan loyalty, with a coefficient of determination test of 0.567. This means that 56.7% of the customer loyalty variable can be explained by the variables of customer satisfaction, service quality, product quality, and price. The remaining 43.3% can be described by other variables that were not examined in this study. Customer satisfaction with loyalty through the t-test hypothesis with a calculated t-value of 5.016, so that H1 is accepted. The quality of service towards loyalty obtained a t-test hypothesis value of 9.172, thus H2 is accepted. Product quality towards customer loyalty through the t-test hypothesis yielded a value of 2.265, thus H3 is accepted. Price towards customer loyalty has a t-statistic value of 8.466, thus H4 is accepted. For future research, the sample studied can be expanded, such as extending the research to all of Indonesia to represent every fan.